Projeto de controlador solar de carga para operação autônoma do Ghost Swimmer® - Lima, José Filipe de (Universidade Federal Rural do Semi-Árido, 2020)
This work aims to develop a load controller using a buck topology CC - CC converter. To track the maximum power point of a 10 W solar panel, which will power a battery for the operation of an aquatic equipment called Ghost Swimmer®, which has the purpose of assessing the performance of amateur and professional swimmers. The design and implementation of the power circuit and the converter controller are presented. A brief review of the method used to track the maximum power point is made. In this work we chose to use the method of incremental conductance. The tracking algorithm was implemented using an Arduino UNO®. The results of the controller project simulation are presented, as well as the results obtained in its implementation, being powered by a 12 V battery and the Ghost Swimmer® itself. The controller has provided adequate operation, supplying the loads that were connected to its output. It was concluded that the controller worked properly, working according to the simulation results.
Keywords: Natação; Conversor CC – CC; Rastreamento do ponto de máxima potência (MPPT); Controlador solar de carga; ENGENHARIAS::ENGENHARIA ELETRICA